Fenomena Lalu Lintas Simpang Bersinyal di Kota Bekasi (Studi Kasus: Simpang Tol Bekasi Timur) - Tama, Yuanda Patria (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
The transportation’s problem that common in Indonesia is a limitation of road space and intersection that needed to conduct the traffic flow. An accident and degradation of intersection’s performance, it’s caused by the driver’s attitude which have a less concern to the traffic law. This research attempt to observe the driver violation which influences the characteristic of urban’s intersection to find out the phenomenon of traffic’s signal intersection. The strategy to design the intersection in East Bekasi highway for reducing driver violation by using the side friction factor that consists of extending the radius of junction sleeves, constructing lay bay in bus stop, demolition the street vendor, ojek base and public transportation. Also, the geometric intersection factor consists of installation signs, marka reparation, constructing the pedestrian facility, and specific stopping area for motorcycle, then the traffic’s characteristic factor consists of an intensive supervising by policeman, constructing the priority track to turn left on red and installation signs.